2015
DOI: 10.12688/f1000research.6393.1
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Pulmonary Alveolar Calcification as a Result of Severe Hypercalcemia due to Acute Lymphoblatic Leukemia.

Abstract: Severe hypercalcemia is a rare metabolic disorder in pediatric medicine. This report describes a rare case of severe hypercalcemia and its clinical manifestations in a 2-year-old toddler. The radiological findings caused by hypercalcemia and osteolysis were emblematic of the osteolytic lesions. Hypercalcemia led to massive pulmonary alveolar calcification. The hypercalcemia was successfully treated with pamidronate, a bisphosphonate drug class. Further investigation resulted in a diagnosis of acute lymphoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 7 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…( 6 ) In addition, the medium- and long-term adverse effects of bisphosphonates have been associated with osteonecrosis of the jaw and ectopic deposition of calcium. ( 7 ) However, to date, no adverse effects related to bisphosphonates have been observed in the described case. Nevertheless, hypocalcemia occurred for 10 days after the initiation of treatment with zoledronate, highlighting the need to monitor serum calcium levels two to four weeks after the initiation of treatment, which is the period of activity of bisphosphonates.…”
mentioning
confidence: 67%
“…( 6 ) In addition, the medium- and long-term adverse effects of bisphosphonates have been associated with osteonecrosis of the jaw and ectopic deposition of calcium. ( 7 ) However, to date, no adverse effects related to bisphosphonates have been observed in the described case. Nevertheless, hypocalcemia occurred for 10 days after the initiation of treatment with zoledronate, highlighting the need to monitor serum calcium levels two to four weeks after the initiation of treatment, which is the period of activity of bisphosphonates.…”
mentioning
confidence: 67%
“…Severe hypercalcemia of malignancy in children has been extensively described in the medical literature. ( 1 ) However, this complication usually presents as a late symptom of acute lymphoblastic disease and not as an early manifestation, as described in a case report by Martins et al ( 2 ) Colleti Junior et al ( 3 ) also observed that hypercalcemia was present as an early symptom of malignancy, and the serum calcium levels were higher than usual (ionic calcium: 2.95mmol/L; normal value: 1.11-1.40mmol/L). In this case, immediately after diagnosis, in addition to hydration and low doses of loop diuretic, treatment was initiated with pamidronate, a bisphosphonate, and resulted in a rapid decrease in the serum calcium levels.…”
mentioning
confidence: 89%
“…Is there a report of calcium deposition in other tissues? In Colleti Junior et al, ( 3 ) a rare alveolar lung deposition was shown on chest computed tomography ( Figure 2 ), and the diagnosis of this symptom was essential during patient follow-up. Therefore, the side effects of treatment with bisphosphonates should be considered.…”
mentioning
confidence: 95%
See 2 more Smart Citations